ADDITIONAL DATA ON LEPIDOPTERA FROM SERBIA - Jakšić, Predrag (Bulletin of Natural Sciences Research, 2018)
This work reports on results from occasional collections in many sites of Serbia in the period 2015-2018., as well as one earlier material from 1982. By more than 50 excursions, from March to October, by day and night and by light traps, a total amount of 45 selected species of Lepidoptera from 10 families were caught. A full list and description of the localities of collection, some color plates and the comment about some species apart relevant are also included.
Keywords: Lepidoptera; Serbia